Space, stars, and the beginning of time : what the Hubble telescope saw - Scott, Elaine, 1940- (Boston : Clarion Books, 2011)
Photographs and text examine the Hubble Space Telescope, discussing how Hubble has helped scientists learn about the universe, and describing how scientists have used the telescope to discover new galaxies, verify the existence of dark energy, and related topics.
The spyglass grows up -- A final visit to the Hubble -- The beginning of time -- The dark forces and black holes -- The life cycle of a star -- Recipe for a planet.
Includes bibliographical references (p. [63]) and index.
Bulletin (Center for Children's books)
Horn Book
School Library Journal
Bulletin (Center for Children's books), February 2011
Horn Book, March 2011
Keywords: Hubble Space Telescope (Spacecraft) -- Juvenile literature; Hubble Space Telescope (Spacecraft); Hubble Space Telescope (Spacecraft); Space telescopes; Space vehicles; Space vehicles; Telescopes